RELASI KUASA DALAM BUKU PANDUAN GURU: IMPLIKASINYA PADA PEMBELAJARAN LITERASI MEMBACA - Mustopa, Rizki Akbar; Dadang S. Anshori (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Abstract Teachers and students are consistently associated within the discourse of education. An ideal classroom environment is one in which power between teachers and students is balanced, allowing learning to occur without rigidity or anxiety, thereby achieving instructional objectives. Ideally, teacher manuals—as guides for classroom instruction—should reflect this balanced teacher-student power relationship. However, in practice, communication within instructional contexts still reveals the dominance of teachers, which tends to limit students' agency in the classroom. This study aims to uncover and describe the teacher-student power relations as represented in Indonesian language teaching manuals for teachers. Three teacher manuals for grades X, XI, and XII were analyzed descriptively using a qualitative approach and discourse analysis, particularly Ruth Wodak’s Critical Discourse Analysis (CDA). The findings indicate that teacher-student power relations are unequal. Teachers are portrayed as holding stronger authority than students. In the texts, the term teacher frequently occupies the subject position and is depicted as the assigner of tasks or commands, with the authority to judge or validate knowledge. Meanwhile, the term student commonly appears as the object acted upon by the teacher-subject verbs. The teacher’s position and authority are illustrated as superior to those of students, evident in the use of the label teacher in task constructions, whereas students are referred to using the pronouns -mu and kamu (“your” and “you”). The implications of these findings for reading literacy instruction are discussed in this paper. Keywords: Critical Discourse Analysis, power relations, discourse analysis, literacy, reading instruction